Analisis Hubungan Antara Tingkat Kecepatan Terhadap Luaran Emisi Gas CO Pada Beberapa Sepeda Motor Matic - Danila Desti Ramadhan; Cahya Maulidta Rohman; Fariz Pradhana Adil Fadzilah; Muchammad Sholiqin; Siti Rachmawati (DPPM Universitas Pelita Bangsa, 2022)
One of the causes of congestion on the highway is the increasing number of motorized vehicle users, whose percentage is now increasing from the use of other vehicles or transportation. Every vehicle in circulation also comes from companies and with various brands. This study aims to determine the comparison of emissions or pressure produced at three constant speeds by five motorized vehicles with different brands using the same type of fuel, to determine the amount of emissions released by each vehicle brand and every hour, and the impact of the resulting emissions on environmental health. . The research was conducted using a quantitative descriptive method with a sampling technique and the data were then analyzed with a literature review and information obtained from the STNK. From this research, it is found that different motorcycle brands with the same year of production have different emission results. Of the five types of brands tested, motorized vehicles with the Beat 110 CC brand and the year of engine production being longer than the other four types produced fewer gas emissions, namely 3237 at a speed of 60 KM/hour. In addition, the pressure (ppm) on the Beat brand will also be lower, although the speed that is different from the other four brands will actually increase the pressure. For the value of emissions issued per hour will also be in line with pressure (ppm). Gas emissions released by motorized vehicles themselves have a harmful impact on health and the environment. One of the dangers posed by vehicle exhaust gases for health and the environment is the increase in hemoglobin levels in the blood which will form COHb in the body. Keywords: CO Gas, Emissions, Motorcycles.